A 100 Myr history of the carbon cycle based on the 400 kyr cycle in marine δ13C benthic records. (20th December 2014) - Paillard, Didier; Donnadieu, Yannick
Abstract Documenting the past coevolution of Earth temperatures and of the carbon cycle is of paramount importance for our understanding of climate dynamics. Atmospheric CO2 is well constrained over the last million years through direct measurements in air bubbles from Antarctic ice cores. For older times, many different and sometimes conflicting proxies have been suggested. Here we provide a new methodology to constrain the carbon cycle in the past, based on marine benthic δ13C records. Marine δ13C data are recording a persistent 400 kyr cycle, with an amplitude primarily linked to the total amount of carbon in the ocean, or dissolved inorganic carbon (DIC). By extracting this amplitude from published records, we obtain a new strong constraint on the 100 Myr history of Earth's carbon cycle. The obtained Cenozoic evolution of DIC is in surprisingly in a good agreement with existing reconstructions of pCO2, suggesting that pCO2 is mostly driven by DIC changes over this period. In contrast, we find no strong decreasing trend in DIC between the Cretaceous and the Cenozoic, suggesting that Cretaceous atmospheric pCO2 levels were limited, and high temperatures at this time should be explained by other mechanisms. Alternatively, high Cretaceous atmospheric pCO2 could occur as a consequence of changes in oceanic chemistry but not carbon content.